Supply Chain Development of Photovoltaic Energy System: A Critical Analysis of the Consumer's Role - Case Study Ghana - Tham-Mbiah, Benjamin Edwin (My University, 2015)
The rising energy problems in Ghana and the need for solutions called for this research. The alternative solution to this problem is renewable energy such as solar photovoltaic systems. Although solar PV systems are in the country its adoption process is slower due to several reasons. This research contributes to a pool of solution by looking at the supply chain of PV systems through the eyes of the consumer, hence the topic; Supply chain development of photovoltaic energy systems: A critical analysis of the consumer’s role – Case study Ghana. The method used for this research was a case study. First a survey was conducted among some solar PV businesses in Ghana to identify the existing supply chain for PV systems and their challenges. Secondly, another survey was conducted among consumers to identify their preferences in solar PV supply chain development. The consumer questionnaires revolved around the four P’s of marketing and supply chain models. The results of the research revealed that the major challenges faced by solar PV business in Ghana were; government policies and finance. On the consumer side, the major challenges faced by them were; finance, education, information awareness and availability of PV’s. The positive side is that consumers want the supply chain to be designed in such a way that PV’s will be available in the nearest retail and distribution centres. Consumers also want PV maintenance specialist centres be established in their communities and education and information to be readily available. In conclusion solar PV businesses have good future prospects in Ghana, only that most consumers are not fully aware of the benefits and prospects of this technology. Secondly, this research recommends that government policies on PV’s be amended to facilitate business. Government and business in Renewable energy industry should co-operate to bring education and to promote consumer awareness. Finally, government should provide incentives on behalf of consumers and businesses for banks and financial institutions to grant soft loans for PV purchases to help solve the energy crisis.
Keywords: Photovoltaic systems; supply chain; consumers; renewable energy; Ghana; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|